DUAL-DOMAIN STIMULATION: THE EFFECTIVENESS OF NUMBER CARDS IN EARLY CHILDHOOD COGNITIVE AND MOTOR DEVELOPMENT - Istirokah, Istirokah; Hidayatullah, Syarif; Hartati, Sulis Janu; Widayat, Edy; Huda, Nuril; Simanjuntak, Nensy Megawati (PRASI, 2025)
Early childhood education is essential for developing children's cognitive potential, particularly in understanding number concepts. Observations at Group A TK Dharma Wanita Dermo, Mojoroto, Kediri City showed that 86.7% of students had difficulty recognizing numbers 1–10. This issue was likely caused by the lack of engaging and creative learning media.This study aimed to improve students' cognitive abilities in recognizing number concepts 1–10 through the use of number card media. The research used the Classroom Action Research (CAR) method based on the Kemmis & Taggart model, conducted over two cycles involving stages of planning, action, observation, and reflection. The subjects were 13 Group A students in the 2024/2025 academic year. Data were collected through observation sheets for teacher and student activities and cognitive assessments using a star rating scale. The hypothesis proposed that number card games could enhance students’ ability to recognize numbers. Results indicated significant improvement across the cycles, supporting the hypothesis. The number card games proved to be an effective, engaging medium for improving numerical understanding in early learners. This research offers practical contributions for early childhood educators by demonstrating the importance of using interactive learning tools. The findings suggest that creative, game-based media can enhance cognitive development and increase learning motivation among young children.